Public speaking anxiety in podcast aided language classes - Ainol Haryati, Ibrahim; Nuraihan, Mat Daud (IDOSI Publication, 2013)
This paper presents a study on learners' level of anxiety when a podcast was used in developing their public speaking skills. This study employs a quasi-experimental, pretest-posttest nonequivalent control group design where the control group was taught using the traditional method whilst a podcast was used as a teaching aid on the treatment group. The podcast makes it possible for the learners to have an authentic audience for their speaking activities. This study was thus conducted to see what would be the effect of using this facility on the learners. Richmond and McCroskey's (1998) Personal Report of Public Speaking Anxiety (PRPSA) was the instrument used to measure the language learners' level of anxiety. The study found that there was no significant difference between the control and the treatment groups. A reduction in the level of anxiety was observed in all groups.